Sistem Informasi Pariwisata Untuk Memudahkan Wisatawan Dalam Menentukan Rute Perjalanan Berwisata di Kota Pagar Alam Berbasis Web - Fitria ria (LPPM Sekolah Tinggi Teknologi Pagar Alam, 2020)
Abstract: This study aims to create a Web-based Tourism Information System. In conveying about tourism, promotion is still carried out through the mass media of television, newspapers, banners and baleho. The impact is that tourists still find it difficult to determine the planning of a tour in the city of Pagar Alam. The system development method used is the Web Engineering method with five stages of Customer Communication, Planning, Modeling, Construction and Deployment. Therefore, the researcher will create a web-based tourism information system in order to make it easier for tourists to find information such as tourist attraction data, hotel data and restaurant data as well as places that are connected to the google map. With the existence of a web-based information system can help spread promotions to tourists widely to increase tourist visits to the City of Pagar Alam.Keywords: Information Systems, Tourism and Web Engineering